Why She Must Lead (IITM Journal of Business Studies, 2024)
The book is written in the English language.  The average time taken to read a chapter was  one hour and 45 minutes. Gender bias and color bias has always been a  critical social evil in degrading humanity and  equality. It has lead to social injustice and  curbing of creativity and talent of masses. The  creative and hardworking skilled women of color  are not acknowledged and appreciated for their  work which develops resentment and anger  amongst themselves in many countries. Since,  diversity is the soil of our mother Earth; we must  stand together for an empowered future.Why She Must Lead shares Dr Vasudha  Sharma’s personal story of immigrating to  the United States from India fifteen years  ago after her marriage, looking for healthier  opportunities. She interviews many women who  play a vital part in raising questions and forming  solutions regarding the leadership gap.  It is a factual reflection of her evolution into  the non-profit world from a serial entrepreneur.  The book is an assemblage of all aspects of  resourceful thoughts that women of color  require to be unbeaten in today’s scenario.  Vasudha has done a thorough study through  her personal experience and stories from women  leaders. This study can inform the readers with  a broader perspective of work-life experiences  of women of color. Inspired by people she has  met around the world, Dr Vasudha has given  solutions in her book where issues like the pay  gap, broken rungs, and lack of mentorship can  be filtered out methodically, and workplaces can  act to raise the most underrepresented group of  women. The book is flowing in two hundred  and forty six pages and across all the pages, Dr  Vasudha talks about fears, pain, and challenges  with empathy and humility. She inspires the  women of color to challenge the assumptions  and myths and lead and live with a mission.
Keywords: mentorship; empathy; humility; mission